'Moving towards understanding', acceptability of investigations following stillbirth in sub‐Saharan Africa: A grounded theory study. (21st October 2022) - Bedwell, Carol; Danna, Valentina Actis; Lyangenda, Kutemba; Tuwele, Khuzuet; Kuzenza, Flora; Kimaro, Debora; Shayo, Happiness; Petross, Chisomo; Chisuse, Isabella; Heazell, Alexander; Victor, Suresh; Vwalika, Bellington; et al.
Abstract: Objective: To explore the views of women, partners, families, health workers and community leaders of potential investigations to determine the cause(s) of stillbirth, in Malawi, Tanzania and Zambia. Design: Grounded theory. Setting: Tertiary facilities and community settings in Blantyre, Malawi, Mwanza, Tanzania and Mansa, Zambia. Sample: Purposive and theoretical sampling was used to recruit 124 participants: 33 women, 18 partners, 19 family members, 29 health workers and 25 community leaders, across three countries. Methods: Semi‐structured interviews were conducted using a topic guide for focus. Analysis was completed using constant comparative analysis. Sampling ceased at data saturation. Results: Women wanted to know the cause of stillbirth, but this was tempered by their fear of the implications of this knowledge; in particular, the potential for them to be blamed for the death of their baby. There were also concerns about the potential consequences of denying tradition and culture. Non‐invasive investigations were most likely to be accepted on the basis of causing less 'harm' to the baby. Parents' decision‐making was influenced by type of investigation, family and cultural influences and financial cost. Conclusions: Parents want to understand the cause of death, but face emotional, cultural and economic barriers to this. Offering investigations will require these barriers to be addressed, services to be available and a no‐blame culture developed to improve outcomes. Community awareness, education and support for parents in making decisions are vital prior to implementing investigations in these settings. Abstract : Linked article : This article is commented on by Elizabeth M. McClure and Robert L. Goldenberg, pp. 68‐69 in this issue. To view this mini commentary visit https://doi.org/10.1111/1471‐0528.17310 .